Artificial Intelligence in Weed Management: Ushering in a New Era of Agricultural Precision - Ali, Sk Asraful; Kaur, Ramanjit; Nithinkumar, Kadagonda; Sankati, Jhonsonraju; Kumar, Sunil; Prajapati, Sunil Kumar; Sahoo, Sushree Swetalika (Chronicle of Bioresource Management, 2025)
Weed management remains a major challenge in modern agriculture, directly influencing crop yield, quality, and long-term sustainability. Conventional practices such as manual removal, mechanical methods, and chemical herbicides are often labor-intensive, costly, and environmentally damaging, while also contributing to the growing problem of herbicide resistance. The adoption of Artificial Intelligence (AI) offers a transformative solution by enabling precision, efficiency, and sustainability in weed control. AI-powered systems equipped with imaging, machine vision, and sensor technologies can accurately differentiate weeds from crops, ensuring highly targeted interventions through robotic weeding, smart sprayers, and other advanced tools. These innovations significantly reduce herbicide dependency, lower production costs, and minimize ecological risks while maintaining effective weed suppression. Although challenges such as high initial investment, weather dependency, and regulatory barriers persist, AI-driven weed management holds immense potential to advance sustainable farming, ensuring higher productivity and environmental stewardship.